ANALISIS STRUKTURALISME GENETIKA DRAMA “THE ZOO STORY” KARYA EDWARD ALBEE - Syam, Essy (Universitas Lancang Kuning, 2016)
This writing deals with an analysis of social condition of a society which is reflected in a literary work, a drama, entitles The Zoo Story written by Edward Albee. Thus, this writing analyzes the text by applying Genetic Structuralism which explores the social condition and social elements found in a text. The result shows that social class which is created by a society separates people with certain level in a society. Eventhough there’s no concrete line to show the separation, but it is felt and undergone realistically just like bars which separate animals with their different kinds in a zoo.